Single umbilical artery: A case report - Pradhan, Neelam; Pradhan, Raju (Nepal Journal of Obstetrics and Gynaecology, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A 38 years woman pregnant for the second time was diagnosed as having a fetus with a single umbilical artery while undergoing routine ultrasound at 5 months of pregnancy. Reports of single umbilical artery associated with chromosomal abnormality are about 30%. Luckily no abnormality was found at birth and thereafter in this baby. Key words: single umbilical artery, USG diagnosis and chromosomal abnormality doi:10.3126/njog.v1i2.2400 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 59-60 Nov-Dec 2006